Pengaruh Bagi Hasil, Kurs, Dan Inflasi Terhadap Pertumbuhan Pendapatan Bagi Hasil Nasabah Deposito Mudharabah : Studi Kasus Bank Muamalat Indonesia - Wilda Efrilyati; Nur Ahmadi Bi Rahmani; Laylan Syafina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Profit sharing is the distribution of business results that have been carried out by the parties who entered into the agreement, namely the customer and the sharia bank. In this case, the results of the business carried out by both parties or one party will be divided according to the portion of each party entering into the contractual agreement. The distribution of business results in sharia banking is determined using the ratio. The ratio is a reward agreed upon by both parties in determining the profit sharing of the collaborative effort. This type of research is quantitative research. Quantitative research is research that uses numbers as a data source. In this research the author uses an associative approach. Associative research is research that uses two or more variables one with another variable. The reason researchers use associativity as a research method is because in this research there is a relationship between one variable and another variable with appropriate research indicators. Research shows that there is a positive influence between Profit Sharing on Income Growth. There is a positive influence between the exchange rate on income growth. There is a positive influence between Inflation on Income Growth. There is a positive influence between Profit Sharing, Exchange Rates and Inflation on Income Growth..